1996
DOI: 10.1016/s0022-5223(96)70061-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of reconstructions of the left anterior descending coronary artery in diffuse atherosclerotic lesions

Abstract: Extended revascularizations of the left anterior descending coronary artery increase surgical risk, although not to a statistically significant degree, and should be performed only of necessity. However, once needed, revascularization is a lifesaving procedure with acceptable early and long-term results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 22 publications
1
22
0
4
Order By: Relevance
“…The reported surgical risk of a combined endarterectomy with patch angioplasty was controversial. Tasdemir et al [11] reported non-significant lower rates of MI and mortality, while Fukui et al [1] have demonstrated a statistically significant higher rate of perioperative MI in this subgroup of patients, compared to those benefiting from angioplasty alone.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…The reported surgical risk of a combined endarterectomy with patch angioplasty was controversial. Tasdemir et al [11] reported non-significant lower rates of MI and mortality, while Fukui et al [1] have demonstrated a statistically significant higher rate of perioperative MI in this subgroup of patients, compared to those benefiting from angioplasty alone.…”
Section: Discussionmentioning
confidence: 87%
“…We are still reluctant to combine endarterectomy to our technique, even if the early as well as the late results of more recent series have been acceptable and that the whole procedure can be safely performed off-pump [1,11,13,14]. We still believe that in part, endarterectomy will add complexity to surgery for the need of a longer arteriotomy, more operative time, more blood loss and increased hospital mortality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations